Highbrow Culture in Politics - Wilk-Suwa, Ilona (Emocje i polityka. Sceny z życia polskiego parlamentu, 2016)
Quoting other peopleʼs arguments by politicians, to rely on someone elseʼs work is rarely seen, but often causing extreme emotions. Recalling (especially inaccurate) the fragment from foreign language authors can cause misunderstanding, confusion of content and change the original meaning. The rhetorical device of this kind can be traced and watched several times by access to the media, what was done in our sociological analysis. Politicians, like actors, through the selection of specific measures of self-presentation (in this case, quotations from literature, cite the author of the widely known) provide customers reality as amended, such that they would like to be seen (Goffman 2008). The analyzed verbal speech in the Sejm were characterized by a strong emotional tone and illustrates language, that is far from the classical canons of savoir vivre (Marcjanik 2014; Achtelik, Tambor 2013). Verbal bon ton in parliament has, through its application, fulfilled many functions, from polite sarcasm through the manifesto of the supremacy, to the personal presentation of erudition. At the outset, the author describes leading concepts used in the chapter. In the next part the author addresses the videos with the participation of politicians who during their public appearances quoted of another authors. In summary the author of the chapter focuses on the function of citations and there are taken into account the positive aspects of using the prose/poetry by individuals elected to public office.